Cost-Effectiveness of Bevacizumab Biosimilar LY01008 Combined With Chemotherapy as First-Line Treatment for Chinese Patients With Advanced or Recurrent Nonsquamous Non-Small Cell Lung Cancer - Luo, Xia; Liu, Qiao; Zhou, Zhen; Yi, Lidan; Peng, Liubao; Wan, Xiaomin; Zeng, Xiaohui; Tan, Chongqing; Li, Sini (Frontiers in Pharmacology, 2022)
Objective To investigate whether LY01008, a local-developed bevacizumab biosimilar, is appropriate for widespread use among Chinese advanced or recurrent nonsquamous non-small cell lung cancer (NSCLC), our current study was designed to evaluate the cost-effectiveness of fist-line LY01008 combined with platinum-doublet chemotherapy versus chemotherapy alone from the perspective of Chinese health care system. Material and Methods This economic evaluation designed a Markov model to compare the healthcare cost and quality-adjusted life-year (QALY) of fist-line LY01008 plus chemotherapy versus first-line chemotherapy. Transition probabilities, including disease progression, survival, and adverse events (AEs)-related discontinuation of first-line treatment, were estimated using data from the clinical trials. Costs and health utilities were derived from local databases, hospitals and published literature. Our base case analysis and scenario analysis focused on the cost-effectiveness of chemotherapy combined with a clinical trial dosage (15 mg/kg every 3-week cycle) and a real-world dosage (7.5 mg/kg every 3-week cycle) of LY01008, respectively. Results In the base case analysis, first-line LY01008 plus chemotherapy was associated with an increase in effectiveness of 0.48 QALYs (2.11 vs 1.63 QALYs) and an increased in healthcare cost of $26,240 ($49,182 vs $22,943) compared with first-line chemotherapy, resulting an incremental cost-effectiveness ratio (ICER) of 54,430/QALY. In the scenario analysis, first-line LY01008 plus chemotherapy was associated with a mean healthcare cost of $38,429, resulting an ICER of 32,125/QALY between first-line LY01008 plus chemotherapy versus first-line chemotherapy. The parameters that determine the cost of LY01008 have the greatest impact on the cost-effectiveness results. Conclusion From the perspective of the Chinese healthcare system, first-line LY01008 at a real-world dosage plus chemotherapy is likely to represent a cost-effective strategy compared with first-line chemotherapy alone for Chinese advanced or recurrent nonsquamous NSCLC patients.